Teacher Factors and Students’ Attitude to Literature in English in Ayedaade Local Government Area of Osun State, Nigeria - Olatunji, Sheriff Olamide (International Journal of Social Learning (IJSL), 2024)
The study investigated teacher factors and students' attitudes to Literature in English. The research focuses mainly on Ayedaade Local Government Area, Osun State. Two hundred SS II students and 20 teachers of Literature in English participated in the study. Teacher-Student Relationship Observation Schedule, Teacher Motivation Questionnaire, Teacher Teaching Style Observation Schedule, and Students’ Attitude to Literature in English Questionnaire were used for data collection. The study showed a negative, insignificant relationship between teacher-student relationships and students' attitudes. The positive, low, non-significant relationship existed between teacher motivation teaching style and students' attitude. Based on the findings of this study, it was recommended that teachers should be trained and equipped with classroom engagement skills that would enable them to communicate effectively with the students.